2016
DOI: 10.1016/j.chom.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A Broad RNA Virus Survey Reveals Both miRNA Dependence and Functional Sequestration

Abstract: Small non-coding RNAs have emerged as key modulators of viral infection. However, with the exception of hepatitis C virus, which requires the liver-specific microRNA (miRNA)-122, the interactions of RNA viruses with host miRNAs remain poorly characterized. Here, we used crosslinking immunoprecipitation (CLIP) of the Argonaute (AGO) proteins to characterize strengths and specificities of miRNA interactions in the context of 15 different RNA virus infections, including several clinically relevant pathogens. Nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
168
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(170 citation statements)
references
References 56 publications
1
168
0
1
Order By: Relevance
“…On the other hand, miR-17 enhances the infection of HeV as well as RSV, suggesting that the pro-viral effects of miR-17 are broadly applied to the paramyxovirus family, and perhaps beyond this family. For instance, miR-17 has recently been shown to be critical for the replication of pestiviruses, primarily via enhancing viral translation and vRNA stability [12]. Cross-referencing of results from the siRNA screen of host genes associated with HeV infection suggests that miR-181 and miR-17~93 target multiple host genes which are anti-viral for HeV, and that the net outcome of cellular expression of miR-181 or miR-17~93 is likely a host microenvironment that is more conducive for henipavirus infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, miR-17 enhances the infection of HeV as well as RSV, suggesting that the pro-viral effects of miR-17 are broadly applied to the paramyxovirus family, and perhaps beyond this family. For instance, miR-17 has recently been shown to be critical for the replication of pestiviruses, primarily via enhancing viral translation and vRNA stability [12]. Cross-referencing of results from the siRNA screen of host genes associated with HeV infection suggests that miR-181 and miR-17~93 target multiple host genes which are anti-viral for HeV, and that the net outcome of cellular expression of miR-181 or miR-17~93 is likely a host microenvironment that is more conducive for henipavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Trobaugh et al showed that the alphavirus Eastern equine encephalitis virus (EEEV) utilizes host-derived miR-142-3p to define cell tropism and to suppress innate immunity, indirectly promoting neuropathogenesis [11]. A comprehensive survey of 15 RNA viruses from 7 families identified miR-17 and let-7 binding to pestivirus 3’ UTR as critical for enhanced viral translation, RNA stability and virus production [12]. The Argonaute protein, a key component of functional miRNA complexes, was also found to be associated with viral RNA of virtually all of the viruses assessed, including paramyxoviruses [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When applied with RNA-induced silencing complex (RISC) factor Argonaute (AGO), AGO HITS-CLIP allows for empirical mapping of miRNA targeting events through isolation of endogenous AGO:miRNA:mRNA (ternary) complexes (Chi et al, 2009, Moore et al, 2014. Application of AGO HITS-CLIP was instrumental for the discovery of novel miRNA mechanisms in unique biological contexts, including coordinate control of viral latency, viral sequestration of host miRNAs, viral genome propagation by 3'UTR targeting (Riley et al, 2012;Luna et al, 2015;Scheel et al, 2016), and cell invasion networks in cancer (Bracken et al, 2014). Recent modification of CLIP (CLEAR-CLIP) utilizes covalent ligation of RNAs within AGO ternary complexes to garner miRNA-target chimeras for the precise identification of in vivo miRNA targeting events in mammalian tissues (Moore et al, 2015).…”
Section: Introductionmentioning
confidence: 99%